Efektifitas intervensi slow stroke back massage terhadap pasien stroke hemoragik - Nusyaibah, Fathunnisa Imarah; Lengga, Vivop Marti (JOURNAL OF Qualitative Health Research & Case Studies Reports, 2026)
Background: Hemorrhagic stroke is a stroke that occurs due to bleeding in the brain due to blood vessel damage. Hypertension is the main risk factor for hemorrhagic stroke. The nursing diagnosis that emerged was "Decreased intracranial adaptive capacity related to hypertension," characterized by high blood pressure, dizziness and persistent headaches, and weakness of the right upper and lower extremities. Purpose: To describe nursing care for decreased intracranial adaptive capacity in hemorrhagic stroke patients, including nursing assessment and evaluation, with the provision of Slow Stroke Back Massage Therapy interventions. Method: This research used a descriptive method with a case study technique and was conducted in March 2023 in the Umar Bin Khatab II Ward of Al-Ihsan Regional Hospital, West Java Province. Results: The assessment phase for a patient managed for a nursing diagnosis of decreased intracranial adaptive capacity revealed uncontrolled hypertension leading to hemorrhagic stroke. Nursing planning was based on the Indonesian Nursing Outcome Standards and interventions based on Evidence-Based Practice. This intervention was administered according to the guidelines, with the primary intervention being Slow Stroke Back Massage (SSBM). Conclusion: The intervention demonstrated a decrease in blood pressure. Slow Stroke Back Massage (SSBM) has been shown to reduce blood pressure, a risk factor for the nursing diagnosis of decreased intracranial adaptive capacity.   Keywords: Hemorrhagic Stroke; Nursing Care; Slow Stroke Back Massage.   Pendahuluan: Stroke hemoragik merupakan stroke yang terjadi karena adanya perdarahan di otak karena kerusakan pembuluh darah. Hipertensi merupakan faktor risiko utama pencetus stroke hemoragik. Diagnosis keperawatan yang muncul yaitu Penurunan kapasitas adaptif intrakranial berhubungan dengan hipertensi ditandai dengan tekanan darah tinggi, pusing dan nyeri kepala terus menerus, ekstremitas kanan atas dan bawah mengalami kelemahan. Tujuan: Untuk mendeskripsikan asuhan keperawatan penurunan kapasitas adaptif intrakranial pada pasien stroke hemoragik meliputi pengkajian keperawatan hingga evaluasi keperawatan dengan pemberian intervensi Terapi Slow Stroke Back Massage. Metode: Penelitian ini menggunakan metode deskriptif dengan teknik studi kasus yang dilaksanakan pada Maret 2023 di Ruang Umar Bin Khatab II RSUD Al-Ihsan Provinsi Jawa Barat. Hasil: Tahapan pengkajian didapatkan pada pasien kelolaan masalah keperawatan penurunan kapasitas adaptif intrakranial didapatkan pasien mengalami hipertensi tidak dikontrol yang menyebabkan stroke hemoragik. Perencanaan keperawatan disusun berdasarkan acuan dari Standar Luaran Keperawatan Indonesia dan intervensi berdasarkan Evidance Based Practice. Intervensi ini diberikan sesuai pedoman yaitu intervensi utama pemberian Terapi Slow Stroke Back Massage(SSBM). Simpulan: Pemberian intervensi menunjukkan hasil evaluasi adanya penurunan tekanan darah. Pemberian intervensi Slow Stroke Back Massage (SSBM) terbukti dalam menurunkan tekanan darah yang merupakan faktor risiko dari diagnosa keperawatan penurunan kapasitas adaptif intrakranial.   Kata Kunci : Asuhan Keperawatan; Slow Stroke Back Massage; Stroke Hemoragik.